'Quit while you are ahead – and smell the roses!' A survey of retired Fellows of the Australian and New Zealand College of Anaesthetists. Issue 5 (September 2021) - Strange Khursandi, Diana; Eley, Victoria
There are no published data on the age of retirement of anaesthetists in Australia and New Zealand. We surveyed 622 retired Fellows of the Australian and New Zealand College of Anaesthetists to determine their ages of complete retirement from clinical practice, demographics, and whether they had retired at the age they had intended to retire. We also aimed to explore factors affecting the decision to retire, the practice of 'winding down', common post-retirement activities, and the arrangement of personal and professional affairs. Responses were received from 371 specialists (response rate 60%). The mean (standard deviation) age of retirement was 65.2 (6.9) years. The mean (standard deviation) retirement ages ranged from 62.0 (7.1) years (those who retired earlier than planned) to 68.2 (4.3) years (those who retired later than they had intended). The mean (standard deviation) age of retirement of the male respondents was 66.0 (6.5) years, and for female respondents was 62.7 (7.7) years. Two hundred and thirty-three respondents (63%) reported winding down their practice prior to retirement, and 360 (97%) had made a will. Poor health and loss of confidence were the two most common factors in the retirement decisions of those who retired earlier than they had planned. Our results may assist current practitioners plan for retirement, and suggest strategies to help health services, departments and private groups accommodate individuals in winding down their practice.